Prevalence and Infection Patterns of Geo-Helminthiasis in a Rural Community along River Okumeshi, Delta State, Nigeria: A Cross-Sectional Study - Nmor, Jephtha C (International Journal of Medical and Health Sciences Research, 2014)
Background: Information on geo-helminth infections in Akoku community has never been reported. This cross-sectional study was conducted to assess the prevalence and pattern of geo-helminth infections among this population, and to evaluate the impact of water source and faecal disposal system on the prevalence of geo-helminth infection. Methods: Stool samples from 300 children aged between 0 and 15 year were screened for the presence of geo-helminth infections using direct smear method and kato-katz techniques. Results: 240(80.0%) children were infected and a triad pattern of Ascaris lumbricoides (156, 52.0 %), hookworm (48, 16.0%) and Trichuris trichiura (36, 12.0%) were observed. There was no sex disparity and no significant difference (p>0.5) in the prevalence of geo-heminthiasis. Prevalence was highest among age group of 0-5 years, infection rate decreasing with increasing age. Multiple helminth infection was highest for A. lumbricoides and Hookworms combination (24, 10.0%). There was significant difference in multiple parasitic infections (P < 0.05). Those subjects using stream water were more infected compared to those using well and pipe bone water (P < 0.05) and those using nearby bushes as source of disposal of faeces were more significantly affected (P < 0.05). Conclusion: The high prevalence of geo-helminth infections suggests that parasitic infections are important public health problems. Thus, enhancing socioeconomic status, improving sanitation facilities, instilling health education and promoting ways of keeping personal hygiene can be good strategies to control these infections in the area.